A study on X chromosome reactivation using iXist - Lai, Lan Tian (2017)
Female mammals inactivate one of the two X chromosomes in each somatic cell in order to balance the X-linked gene dosage between females and males (X chromosome inactivation, XCI). This process is mediated by non-coding RNA X inactive specific transcript (Xist). Here, I show that, when embryonic stem (ES) cells were cultured under undifferentiated condition, inducible Xist was sufficient to silence genes in vitro. Furthermore, the induced XCI was counteracted by the endogenous capability of X chromosome reactivation (XCR) in the pluripotent ES cells. Thus, perturbing XCR players should tip the balance towards stronger gene silencing effects. Using this experimental system, we show that shRNA knock- down of histone acetyltransferase Kat8 and its associated protein from Male Specific Lethal (MSL) complex, Msl2, significantly enhanced the gene silencing effect of induced XCI in undifferentiated ES cells. Interestingly, Kat8 and Msl2 are involved in Drosophila dosage compensation by up-regulating X-linked gene expression from the single X chromosome in males. Through immuno-RNA FISH, we also show that induced XCI caused Kat8 exclusion from the X chromosome territory. Moreover, the exclusion also occurred to Histone 4 Lysine 16 hypoacetylation (H4K16ac), the histone modification associated to Kat8 enzyme activity. Taken together, our results show that Kat8 and Msl2 are involved in mammalian XCR.